PENGARUH EKSTRAK ETANOL PEGAGAN (Centella asiatica) TERHADAP KADAR SITOKIN PROINFLAMATOTIK-a DAN SITOKIN ANTIINFLAMATORIK IL-10 DI HIPPOCAMPUS TIKUS PASCASTRES LISTRIK 28 HARI - , IKA MURTI HARINI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: After chronic stress, there arean increase the level ofproinflammatorycytokines TNF-αand alsodecrease the level ofantiinflammatorycytokinesIL- 10 inrathippocampus.Centellaasiaticaisone of herbal plantswhichhaveneuroprotectiveand anti-inflammatory effect.There are nostudieswhich investigate the effectsof Centellaasiaticaon levels of TNF- α andIL-10 in therathippocampus after 28 days electrical stress. Objectives : Thisstudyaimstoinvestigate the effectof Centellaasiaticaleaf ethanolic extract(CA) on thelevel of proinflamatorycytokinesTNF-α andantiinflamatorycytokineIL-10 in therathippocampusafter28 days electrical stress. MaterialsandMethods : Thirtymalerats (SpragueDawley) weredividedintosixgroups: nonstress normal control (A), stress + distilled water (B), nonstress +CA 300mg/kg/d (C), stress +CAdose 150 mg/kg/d (D), stress +CA 300 mg/kg/d (E), stress +CA600 mg/kg/d (F). After 28 days, the rats were sacrificed and the hippocampus was dissected out. Hippocampal protein was isolated and the levels of TNF and IL-10 were measured by ELISA. Results : The level ofTNF-αinstressedrats(B, 6,37 ± 0,39 pg/mL)washigherthan normal control (A 5.43 ±0.11, p<0.05). The stressedgroups received CA had lower level of TNF-α (i.e(D)5,92 ± 0,14 pg/mL